2018
DOI: 10.1016/j.scitotenv.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil washing with biodegradable chelators on the toxicity of residual metals and soil biological properties

Abstract: Soil washing with chelators is a promising and efficient method of remediating metals-contaminated soils. However, the toxicity of residual metals and the effects on soil microbial properties have remained largely unknown after washing. In this study, we employed four biodegradable chelators for removal of metals from contaminated soils: iminodisuccinic acid (ISA), glutamate-N,N-diacetic acid (GLDA), glucomonocarbonic acid (GCA), and polyaspartic acid (PASP). The maximum removal efficiencies for Cd, Pb, and Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(28 citation statements)
references
References 55 publications
(100 reference statements)
2
23
0
Order By: Relevance
“…Hu et al [200] achieved removal of 73% Pb using EDTA as a chelating agent. Wang et al [201] used iminodisuccinic acid, glutamate-N, N-diacetic acid, glucomonocarbonic acid, and polyaspartic acid to extract 53% and 55% Pb from Pb-Zn contaminated soil. However, these technologies have certain hurdles for their practical utility due to change in soil properties, loss of nutrients, adverse effect of washing chemicals, generation of wastewater, and cost of chemicals and their negative impact on the environment.…”
Section: Soil Washingmentioning
confidence: 99%
“…Hu et al [200] achieved removal of 73% Pb using EDTA as a chelating agent. Wang et al [201] used iminodisuccinic acid, glutamate-N, N-diacetic acid, glucomonocarbonic acid, and polyaspartic acid to extract 53% and 55% Pb from Pb-Zn contaminated soil. However, these technologies have certain hurdles for their practical utility due to change in soil properties, loss of nutrients, adverse effect of washing chemicals, generation of wastewater, and cost of chemicals and their negative impact on the environment.…”
Section: Soil Washingmentioning
confidence: 99%
“…It is frequently used for removing PTEs with soil washing (Golmaei et al, 2018;Sawai et al, 2017) but has been criticized because of its poor biodegradability and its persistence in soil (Mu'azu et al, 2018;Wang et al, 2016). [S,S]eethylenediaminedisuccinic acid (EDDS) has been proposed as an environmentallyefriendly substitute for EDTA (Beiyuan et al, 2017(Beiyuan et al, , 2018Yoo et al, 2018) because it is very biodegradable and gives comparable soil washing efficiencies to EDTA (Wang et al, 2018). However, more ecoefriendly and effective biodegradable chelators for soil washing are still desired (Mu'azu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable chelators such as polyaspartic acid (PASP) (Mu'azu et al, 2018;Fu et al, 2017), glutamateeN,Nediacetic acid (GLDA) (Tang et al, 2017;Suanon et al, 2016;Wang et al, 2016), iminodisuccinic acid (ISA) (Wu et al, 2015), and glucomonocarbonic acid (GCA) (Wang et al, 2018) have been described in many publications because they are biodegradable and have low toxicities (Pinto et al, 2014;Sawai et al, 2017). PASP and GCA are much more biodegradable than other common chelators such as EDTA (Wang et al, 2018;Mu'azu et al, 2018), and more that 60% of GLDA (Suanon et al, 2016) and ISA (Wu et al, 2015) in soils has been found to degrade within 28 d. Moreover, like other biodegradable chelators, and in contrast to strong acid or basic solutions, these chelators generally affect the soil composition, aggregate structure, and the fertility level little (Komínkov a et al, 2018;Wang et al, 2018). In addition, because they contain different types and amounts of groups (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations